The readiness of FTMSK students towards the implementation of mobile learning in learning C++ programming language / Khairu Faradilla Mohd Zaini - Mohd Zaini, Khairu Faradilla (2007)
Mobile devices are gaining popularity among youngsters nowadays. Emerging mobile devices provide opportunities for new kinds of support for teaching and learning but also pose challenges. In FTMSK, there is lack of studies to investigate the readiness of the students towards the implementation of mobile learning in C++ programming language. The research on educational potential of mobile devices also is lacking in FTMSK. Therefore, this paper primarily aims to determine the readiness of FTMSK students towards the implementation of mobile learning in learning C++ programming language, as well as to identify the advantages and disadvantages of mobile devices for educational purposes. The methodology that has been used to achieve the objectives of the project are through survey questionnaires and from the literature reviews. Data that has been collected and analysed showed that most of the respondents are ready to implement mobile learning in learning C++ programming language since majority of them like to learn using technology (85 %), interested to know more about mobile learning (75%) and agree if mobile learning is implemented in learning C++ programming language (90 %). 80 % of the respondents agree with the following advantages and disadvantages of mobile devices for educational purposes. The advantages are ; learners can interact with each other and with the practitioner instead of hiding behind large monitors, It is much easier to accommodate several mobile devices in a classroom than several desktop computers, PDAs or tablets holding notes and e-books are lighter and less bulky than bags full of files, paper and textbook, or even laptops, handwriting with the stylus pen is more intuitive than using keyboard and mouse, it is possible to share assignments and work collaboratively, mobile devices can be used anywhere, anytime including at home, on the train and in hotels, can take notes directly into the device during outdoor lessons or on field trips, can draw diagrams, maps, sketches directly onto a tablet using standard software, stylus pens are much more natural for web browsing, and lastly can increases motivation and personal commitment to learn if a student can “own” a device to encourages responsibility. The disadvantages of mobile devices for educational purposes are; small screens limit the amount and type of information that can be displayed, limited storage capacities, batteries require regular charging, and data can be lost on some devices if this is not done correctly, lack of common platform, more easily lost or stolen than desktops, much less robust than desktops, fast-moving market so devices can become out of date very quickly, security issues when accessing wireless networks via mobile devices, practitioners may require extra training in order to be able to use the devices effectively and lastly difficulties with printing, unless connected to a network.